2015
DOI: 10.4236/oje.2015.511045
|View full text |Cite
|
Sign up to set email alerts
|

Germination Behaviour of a Perennial Amaranthaceae of North Western Algeria (Oran): <i>Arthrocnemum glaucum</i> (Del.) Ung. Respectively Submitted to Thermal Factor and Salt Stress

Abstract: In light of the importance of seeds germinative phase in the progress of later stages of development of any particular plant species in semi-arid and arid area, it is essential to study the germinative behavior and to evaluate the tolerance of a perennial halophyte of Amaranthacaea family, Arthrocnemum glaucum (Del.) Ung. during this crucial phase. A study is devoted to this species seeds germination, which although it's a mandatory halophyte, it's less tolerant to salt stress in germination' phase. Germinativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Another type of previous treatment to promote germination has been based on its exposure to a certain period of cold. [48] found that without a seed priming treatment the germination percentage in Arthrocnemum plants collected from northern Algeria was quite low, ranging from 5 to 30% depending on the germination temperature (30% to 40ºC). To achieve an improvement in germination, they exposed the seeds to a cold pretreatment without salinity regime (5ºC for 2, 10 and 27 weeks) and the germination percentages increased 30%, 40% and 80% respectively.…”
Section: Seed Priming Treatment On Arthrocnemum Germinationmentioning
confidence: 98%
See 2 more Smart Citations
“…Another type of previous treatment to promote germination has been based on its exposure to a certain period of cold. [48] found that without a seed priming treatment the germination percentage in Arthrocnemum plants collected from northern Algeria was quite low, ranging from 5 to 30% depending on the germination temperature (30% to 40ºC). To achieve an improvement in germination, they exposed the seeds to a cold pretreatment without salinity regime (5ºC for 2, 10 and 27 weeks) and the germination percentages increased 30%, 40% and 80% respectively.…”
Section: Seed Priming Treatment On Arthrocnemum Germinationmentioning
confidence: 98%
“…In traditional studies on tolerance of seeds to salinity without enforced dormancy pretreatments under these stress conditions, it has been shown that in Arthrocnemum, germination is reduced due to an increase in salinity and, normally, the untreated control produced higher germination percentages [23,27,40,43,44,46,48,49,56]. The first germination test on Arthrocnemum found in the literature was performed by [56] from the "Le cap Croisette" (southern Marseille, France).…”
Section: Seed Priming Treatment On Arthrocnemum Germinationmentioning
confidence: 99%
See 1 more Smart Citation